STRATEGI HUBUNGAN MASYARAKAT GMPI MELALUI CORPORATE SOCIAL RESPONSIBILITY DALAM MEMBENTUK CITRASTRATEGI HUBUNGAN MASYARAKAT GMPI MELALUI CORPORATE SOCIAL RESPONSIBILITY DALAM MEMBENTUK CITRA - Auereal, Cantika; Widyasanty, Gita (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
The role of Public Relations has a strategy so that the community can assess, appreciate, support, and sympathize with the organization. Judgments based on people's point of view can be said to be imagery. One of the tasks of Public Relations that can shape the image is to carry out Corporate Social Responsibility programs as a form of commitment carried out by the organization is expected to be able to shape and improve the image of the organization. In this study, we will look at the social programs of the Young Generation of Indonesia's development. The purpose of this study is How GMPI's Public Relations Strategy Through Corporate Social Responsibility in Shaping Image. This research is a constructivist qualitative descriptive research. Data collection techniques with interviews, observations, consistent observation, and documentation. The data used are data obtained from direct interviews with public relations from GMPI, and recipients of assistance from social activities that are routinely carried out every fasting month. The results of this study hope that social activities held regularly every fasting month will be expanded further, and assistance can be provided to remote areas. Social programs that are running are quite good, as evidenced by those who receive help from the smiles they give, and assistance that can help in the month of Ramadan, and the community expects not only social activities, but environmental care activities.